Oral and intratumoral microbiota influence tumor immunity and patient survival - Wei, Kaitong; Ma, Yaqing; Xu, Jing; Hu, Shuijuan; Zheng, Hongyu; Liu, Yuelian; Sun, Qiang (Frontiers in Immunology, 2025)
BackgroundThe aim of this study was to analyze the changes in the oral microbiota of patients with oral squamous cell carcinoma (OSCC) compared to healthy controls and the effect of intratumoral microorganisms on the host immune microenvironment.MethodsSaliva samples were collected from 36 OSCC patients and 34 healthy controls. 16S rDNA sequencing and bioinformatics analysis were conducted on the saliva samples. Differential expression, pathway enrichment, and tumor microenvironment analyses were performed on transcriptome data from head and neck squamous cell carcinoma (HNSCC) in The Cancer Genome Atlas (TCGA) database and OSCC patients in the GEO database.ResultsOral microbiota exhibited comparable α diversity but distinct β diversity between OSCC patients and healthy controls. Capnocytophaga, Flavobacteriaceae, and Vibrionaceae were significantly enriched in the OSCC group. Pathway analysis revealed dysregulation of metabolic pathways, including arginine and proline metabolism and sulfur transfer systems, in the OSCC group. The presence of microorganisms activated immune responses within tumor tissues, and immune scores increased with disease progression. Changes in the abundance of tumor immune-related signaling pathways were significantly associated with patient survival.ConclusionSpecific oral microbiota in OSCC patients may serve as biomarkers for distinguishing OSCC. The interaction between microorganisms and the host alters the tumor immune microenvironment, which provides a theoretical basis for OSCC immunotherapy.